2001
DOI: 10.1103/physrevb.64.245339
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence ofInxGa1xN/et al.

Abstract: The carrier recombination dynamics in a series of In x Ga 1Ϫx N/GaN multiple quantum wells, nominally identical apart from different Si doping concentrations in the GaN barriers, was studied by time-resolved photoluminescence ͑PL͒ with excitation densities ranging from 220 nJ/cm 2 to 28 J/cm 2 at 10 K and 300 K. At early time delays and with excitation densities greater than 5 J/cm 2 , at which the strain-induced piezoelectric field is screened by both photogenerated carriers and electrons from the GaN barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…2(a)] was obtained at the assumption that the built-in electric field inside the QW system results from the piezoelectric and spontaneous polarizations in this system [15,16] with the appropriate periodic boundary conditions [28] (this situation is characterized by a step-like difference in the total polarization at QW interfaces P ). It should be noted that the internal electric field, which results from polarization effects, can be partially screened in our samples because of Si doping in InGaN barriers [29][30][31]. It means that the real built-in electric field is smaller than the electric field corresponding to 100 % P in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a)] was obtained at the assumption that the built-in electric field inside the QW system results from the piezoelectric and spontaneous polarizations in this system [15,16] with the appropriate periodic boundary conditions [28] (this situation is characterized by a step-like difference in the total polarization at QW interfaces P ). It should be noted that the internal electric field, which results from polarization effects, can be partially screened in our samples because of Si doping in InGaN barriers [29][30][31]. It means that the real built-in electric field is smaller than the electric field corresponding to 100 % P in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…where c 31 and a c z are the hydrostatic deformation potentials. ε z is the strain which is defined as ε z = (c −c 0 )/c 0 , where c is the lattice constant of the free-strained crystal (InGaN in this case) and c 0 is the lattice constant of the substrate (GaN).…”
Section: Resultsmentioning
confidence: 99%
“…The blueshift (73 meV at 10 K) of the PL peak in sample B compared with the undoped sample (A) has been widely observed. [3][4][5] The PL peaks of the well-doped sample (C) approximately coincide with those of the undoped sample (A), except the small redshifts below 80 K and above 200 K. All the curves in Fig. 4 show S-shaped variations of the PL peak, which is typical behavior of such clustered and strained structures.…”
Section: Sample Preparation and Experimental Proceduresmentioning
confidence: 62%
“…Typically, with increasing silicon-doping concentration, particularly doping in barriers, the following phenomena were observed: (1) the photoluminescence (PL) peak blue shifted, (2) the Stokes shift (SS) decreased, (3) the PL decay time reduced, and (4) the PL intensity increased. [1][2][3][4][5][6] Such variations in optical properties were usually attributed to the screening of the quantum-confined Stark effect (QCSE) [3][4][5] because of the doped carriers. In other words, the piezoelectric field was effectively reduced with silicon doping through carrier screening.…”
Section: Introductionmentioning
confidence: 99%
“…4. Choi et al 28 reported that the main PL peak blue-shift phenomenon increased with increased excitation density, mostly due to the filling of the band by the photogenerated carriers. When the laser spots were focused on the mesa-edge region in the CSS-LED samples, the PL peak wavelengths varied from 464.2 nm (1 mW) to 453.4 nm (37 mW) with a 10.8-nm blue-shift wavelength, and they mostly stayed constant at 453.4 nm when the excited laser power was increased to more than 25 mW.…”
Section: Resultsmentioning
confidence: 98%